2018
DOI: 10.1136/bmjgh-2018-001018
|View full text |Cite
|
Sign up to set email alerts
|

Digital adherence technologies for the management of tuberculosis therapy: mapping the landscape and research priorities

Abstract: Poor medication adherence may increase rates of loss to follow-up, disease relapse and drug resistance for individuals with active tuberculosis (TB). While TB programmes have historically used directly observed therapy (DOT) to address adherence, concerns have been raised about the patient burden, ethical limitations, effectiveness in improving treatment outcomes and long-term feasibility of DOT for health systems. Digital adherence technologies (DATs)—which include feature phone–based and smartphone-based tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
226
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(229 citation statements)
references
References 90 publications
1
226
1
1
Order By: Relevance
“…Cost-effectiveness is beyond the scope of this analysis; however, a cost-effectiveness analysis of potential ART adherence monitoring interventions in sub-Saharan Africa found that an adherence monitoring-based intervention could cost up to $50 per person-year on ART while remaining cost-effective, mainly driven by savings through effective differentiation of care [8]. Current lower cost versions of real-time adherence monitoring devices consistent with that threshold [40] are now available and are being tested for use in routine care (NCT03825952). Application of a previously developed machine learning tool does not require intensive computing resources [41], and the increasing use of smart phones globally [42] could make even real-time updates to a machine learning algorithm feasible in the foreseeable future.…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effectiveness is beyond the scope of this analysis; however, a cost-effectiveness analysis of potential ART adherence monitoring interventions in sub-Saharan Africa found that an adherence monitoring-based intervention could cost up to $50 per person-year on ART while remaining cost-effective, mainly driven by savings through effective differentiation of care [8]. Current lower cost versions of real-time adherence monitoring devices consistent with that threshold [40] are now available and are being tested for use in routine care (NCT03825952). Application of a previously developed machine learning tool does not require intensive computing resources [41], and the increasing use of smart phones globally [42] could make even real-time updates to a machine learning algorithm feasible in the foreseeable future.…”
Section: Discussionmentioning
confidence: 99%
“…All the adult TB patients diagnosed at three select tuberculosis unit of Bangalore city during the period January-March 2019 were included in the study. The sample size was calculated based on the assumption of treatment success rate among patients with and without mobile application as 80% and 88% respectively [11]. It is calculated with 80% power and 95% confidence interval and was found to be 331 in each group.…”
Section: ) Study Population Sample Size and Sampling Techniquementioning
confidence: 99%
“…This gives rise to a need for more flexible and personalized digital support that takes into account each individual's behavioral drivers and triggers without the need for human analysis. Tailored DATs have great potential to support patients effectively without undue demands on physician time and with much lower costs than traditional telephonebased programs, as demonstrated by a 2018 review of the literature on such technologies with tuberculosis patients 20 as well as a 2019 study with hypertensive patients in the UK. 21 These promising approaches warrant further development, including the design of DAT-friendly profiling tools.…”
Section: Introductionmentioning
confidence: 99%